Determinants of Property and Real Estate Firm Value in Indonesia - Sari, Noor Inayah; Budiman, Nita Andriyani; Salisa, Naila Rizki (LLDIKTI Wilayah 1 Sumatera Utara, 2023)
The firm value is the perception of investors associated with stock prices. Shareholders have an interest in enhancing the company's value to maximize their wealth. This research aims to investigate the influence of dividend policy, profitability, intellectual capital disclosure, free cash flow, and tax avoidance on firm value in property and real estate firms. The population in this study consists of property and real estate companies listed on the Indonesia Stock Exchange from 2015 to 2021. This study employs a purposive sampling technique, resulting in 49 samples. The research method utilizes panel data regression analysis using EViews 12 software as the analytical tool. The findings of this research indicate that profitability, intellectual capital disclosure, and free cash flow have a positive influence on firm value, while dividend policy and tax avoidance do not affect firm value.